Information and Communication Technologies in Modern Education and their Application in the Teaching Process - Rajabova Gulchekhra Salomovna (Global Scientific Publishing, 2025)
This article highlights the role and significance of information and communication technologies (ICT) in the modern educational process. It analyzes opportunities such as improving the quality of education through ICT, organizing the learning process effectively, and increasing student engagement. Additionally, methods of using Learning Management System (LMS) platforms, web technologies, and cloud services in the learning process are discussed. Special emphasis is placed on the widespread application of Google’s cloud services - Google Classroom, Drive, Docs, and Meet - in education. The article aims to enhance the efficiency of teaching by applying technological approaches to modern teaching methods.
Keywords: Information and Communication Technologies; technological approach; interactive lesson